1969
DOI: 10.1139/m69-130
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a protein-lipopolysaccharide complex released from cell walls of Pseudomonas aeruginosa by ethylenediaminetetraacetic acid

Abstract: Results from analytical ultracentrifugal analysis, Sephadex gel filtration, isopycnic density-gradient centrifugation, and polyacrylamide disc-gel electrophoresis revealed that ethylenediaminetetraacetic acid liberated a protein–lipopolysaccharide complex from cell walls of Pseudomonas aeruginosa with an estimated molecular weight of not less than 160 000 and probably about one million. Electron microscopy of this complex revealed spherules and rodlets. The diameter of the former was approximately 70 ± 10 Å wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
62
1

Year Published

1971
1971
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 4 publications
6
62
1
Order By: Relevance
“…This action of EDTA is attributed to the chelation of divalent metals which are required for the structural integrity of the cell envelope (1, 7). Rogers et al (21) demonstrated that a proteinlipopolysaccharide complex is released from the cell envelope by EDTA. Repaske (19) found that EDTA allows lysozyme to attack cell walls of certain bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…This action of EDTA is attributed to the chelation of divalent metals which are required for the structural integrity of the cell envelope (1, 7). Rogers et al (21) demonstrated that a proteinlipopolysaccharide complex is released from the cell envelope by EDTA. Repaske (19) found that EDTA allows lysozyme to attack cell walls of certain bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…For example, LPS mutants which have lost the O antigen component have increased affinity for hydrophobic probes (14,23,25,29,31,32). EDTA treatment of cells has been shown to cause partial release of LPS (4,5,15,30), resulting in cells that are more susceptible to the action of hydrophobic antibiotics (15, 16). The mechanism of EDTA-induced LPS loss is through chelation of divalent cations, namely Mg 2ϩ , which results in a weakening of LPS-LPS interaction and release of LPS to the growth medium (25).…”
mentioning
confidence: 99%
“…Loss of these cations from the cell wall could alter the structure. Rogers et al (14) showed that incubation of P. aeruginosa in EDTA caused the release of protein and lipopolysaccharide from the cell wall. It is suggested that TRIEN dihydrochloride may be acting in a manner similar to that of EDTA by causing an increase in cell permeability, thus allowing gentamicin easier access to its site of action in the cell; or (ii) it is possible that TRIEN dihydrochloride binds divalent cations in the medium only, thus preventing incorporation of the cations into the cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the chelating agent, ethylenediaminetetraacetic acid (EDTA), increases the susceptibility of P. aeruginosa to various antibiotics in vitro (1,17). EDTA has been shown to increase cell wall permeability by removal of calcium, which is involved in essential cross-linkages and cell wall integrity (5,(7)(8)(9)14). However, due to the toxic properties of EDTA, its use in systemic therapy of P. aeruginosa infections has been limited (2).…”
mentioning
confidence: 99%